2013
DOI: 10.3390/ijms140612484
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of 5-Arylidene Thiohydantoin by Sequential Sulfonylation/Desulfination Reaction

Abstract: The sequential sulfonylation/desulfination reactions of 5-benzylthiohydantoin with excess arylsulfonyl chlorides in the presence of triethylamine have been developed to afford a wide range of 5-arylidene thiohydantoin derivatives in moderate to excellent yields. A plausible sulfonylation/desulfination mechanism was proposed. The bioassay showed that these compounds exhibit certain fungicidal activities with the 71.9% inhibition rate of 2K against B. cinerea, and 57.6% inhibition rate of 2m against A. solani, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…cinerea and F . graminearum were evaluated using methods in the references [21,22,23] by the mycelium growth rate and spore germination tests [24,25]. The cultures were incubated at 25 ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…cinerea and F . graminearum were evaluated using methods in the references [21,22,23] by the mycelium growth rate and spore germination tests [24,25]. The cultures were incubated at 25 ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The preliminary fungicidal activities of compounds 5 – 6 against F. graminearum , R. solani , A. solani , S. sclerotiorum , and B. cinerea were evaluated using methods in the references [33,34,35,36,37] by the mycelium growth rate [38]. The culture was incubated at 25 ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The preliminary fungicidal activities of compounds 7 – 9 against F. oxysporurm , A. solani , B. berengeriana , C. arachidcola and F. graminearum were evaluated using methods in the references [7,10] by the mycelium growth rate test [38]. The culture was incubated at 25 ± 0.5 ºC.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these derivatives are very useful building blocks for the synthesis of various heterocycles such as 5-arylidene derivatives of imidazoline-4-one, imidazothiazine, diazinone, and diazepinone [ 7 9 ]. In our laboratory, several types of hydantoin and thiohydantioin derivatives ( 1 , 2 , 3 ) were synthesized, and we showed that some of them exhibit good herbicidal, fungicidal and insecticidal activities [ 10 13 ]. Acylthioureas are the key structural motifs of numerous compounds that displayed a wide range of biological activity such as antimicrobial, antipathogenic, insecticidal, fungicidal, antitumor activities and influenza virus inhibitors [ 14 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation